Diurnal variation of ducts observed over a tropical station, Gadanki, using high‐resolution GPS radiosonde observations. Issue 4 (6th April 2016) - Manjula, G.; Roja Raman, M.; Venkat Ratnam, M.; Chandrasekhar, A. V.; Vijaya Bhaskara Rao, S.
Abstract: A comprehensive study on diurnal variation of ducting using high vertical and temporal resolution radiosonde measurements over the Indian tropical region, Gadanki (13.5°N, 79.2°E), was presented. The diurnal variation of ducts was examined statistically based on both the refractivity and modified refractivity using 3‐hourly radiosonde soundings obtained during October 2010 to March 2014 as a part of tropical tropopause dynamics (TTD) campaigns conducted under Climate and Weather of Sun Earth System (CAWSES) India Phase II program. Strong diurnal variation in the altitude of occurrence of the duct has been found and is at maximum altitude ( 2.5 km) during 11–17 LT. Interestingly, it is found that the occurrence of duct altitude closely follows the boundary layer altitude. Diurnal variation of duct altitude is maximum during postmonsoon followed by winter, monsoon, and minimum in premonsoon. However, duct strength is maximum during winter followed by premonsoon, postmonsoon, and minimum in monsoon. Duct thickness is found to be varying between 0.4 km and 1 km diurnally with the highest thickness during the winter season. Strong diurnal and seasonal variation in the percentage occurrence of the ducts was found with the highest percentage of ducts observed during winter (77%) followed by postmonsoon (51%), premonsoon (44%), and monsoon (10%). All the characteristics of ducts during all the seasons are maximum at 14 LT due to the high solar irradiance over Gadanki from 11 to 17 LT. The minimum frequency being trapped has been investigated and found that wave trapping occurs for the radars with frequencies 56–438 MHz over this station. Key Points: Diurnal variation of ducting using high vertical and temporal resolution radiosonde is presented Strong diurnal variation in the altitude of occurrence of the duct has been found Interestingly, the occurrence of duct altitude closely follows the boundary layer altitude